The effect of an interventional program based on the Theory of Ethology on infant breastfeeding competence - aghdas karimi; Sepideh Bagheri; Talat Khadivzadeh; Khadijeh Mirzaii Najmabadi (Mashhad University of Medical Sciences, 2014)
Introduction: according to the ethology theory mother infant separation immediately after birth can interfere with the infants innate behaviors for the initiation of breastfeeding. The aim of this study was to the effect of an interventional program based on the Theory of Ethology on infant breast feeding competence Materials and Methods: 114 primiparous, Iranian, healthy, full term mothers between 18-35 years with normal vaginal delivery who intended to breastfeed their babies. They were put in direct skin to skin contact with their infants immediately after birth for two hours. Then, rates of infant breastfeeding competence were compared with a control group receiving routine hospital cares. Results: Rates of infant breastfeeding competence were higher in the skin to skin contact group compared to routine care group (p=0.0001). Conclusion: mother- infant early skin to skin contact promotes infants natural feeding behaviors leading to higher rates of infant breastfeeding competence. These findings confirm the Theory of Ethology.